Questions to the external image of the Republic of China in the XXI century. (Journal of Oriental Studies, 2016)
This article discusses aspects of the «internal» and «external» image of modern China. «Factor image» held an important role in the making of China as a major subject of the international relations.
Keywords: Kazakhstan; China; image; «harmonious society»; the Confucius Institute